DAMPAK SINDROM FoMO TERHADAP INTERAKSI SOSIAL PADA REMAJA - Salma Nadzirah; Wahidah Fitriani; Putri Yeni (PASCASARJANA UNISNU, 2022)
The impact of the internet is currently very worrying for teenagers. Both teenagers who are still in school and teenagers who are not in school. One of the consequences of this internet addiction is FoMO Syndrome (Fear of Missing Out) which means a teenager's fear of missing himself in information on various social media such as IG, WA, FB and other applications. From this problem, the most influential impact in the lives of teenagers is the lack of social interaction with the surrounding environment, because they are too busy thinking about updating information on social media.